Filaggrin Defect at Atopic Dermatitis: Modern Treatment Options - Nikolay N. Murashkin; Leonid A. Opryatin; Roman V. Epishev; Alexander I. Materikin; Eduard T. Ambarchian; Roman A. Ivanov; Alena A. Savelova; Roza Y. Nezhvedilova; Lyudmila L. Rusakova ("Paediatrician" Publishers LLC, 2022)
Atopic dermatitis is a common chronic skin disease, its pathogenesis is associated with congenital or acquired deficiency of filaggrin protein. In recent years, extensive evidence on the causes of filaggrin deficiency has been obtained. The structure and functions of this protein are described, that opens new approaches for atopic dermatitis management.